Impact of Organizational Support and Social Capital on University Faculties’ Working Performance - Chen, Zhong; Chen, Dong; Peng, Michael Yao-Ping; Li, Qingchang; Shi, Yangyan; Li, Jialu (Frontiers in Psychology, 2020)
As the major concerns of higher education institutions are teaching, services, and research, this paper describes a nationwide evaluation of institutional performance in relation to universities in Taiwan. The evaluation was based on the perceptions of university professors regarding institutional slack and reputation, as well as internal and external social capital. The study sought answers to several research questions and adopted a survey approach. After choosing 30 universities of various sizes and from different regions, 926 professors were selected randomly as participants. Using a regression model, this study confirms the influence of institutional slack, reputation, and internal and external social capital on performance. The results show that: (a) institutional slack and reputation positively affect institutional performance; (b) internal social capital positively and significantly influences the relationships of institutional slack and reputation with performance; and (c) external social capital has a positive moderating effect on the relationship between institutional slack and performance. Concluding this paper, theoretical and managerial implications and suggestions for future studies are proposed.